ANALISIS LITERATUR MANAJEMEN PENDIDIKAN DALAM PEMIKIRAN KI HADJAR DEWANTARA TERHADAP KOMPETENSI KEWIRAUSAHAAN KEPALA SEKOLAH DI ERA MODERN - Sarah Kustini; Sukarman Sukarman; Muhammad Fauzul Fikri; Ashni Fannida Istina'ima Putri (Pedagogi: Jurnal Ilmiah Pendidikan, 2026)
This research aims to analyze the integration of Ki Hadjar Dewantara’s philosophical thoughts into the development of school principals’ entrepreneurial competencies within the context of modern education. In an era of global disruption, school principals are required to transcend traditional administrative roles, evolving into independent innovators capable of calculated risk-taking. However, contemporary entrepreneurial models often risk drifting toward pure commercialization. This study employs a qualitative library research method, utilizing content analysis to examine the primary works of Ki Hadjar Dewantara alongside contemporary educational management literature. The findings indicate that school principals’ entrepreneurial competence is deeply rooted in the concept of “Independence” (Kemandirian) and the “Trikon” principles (Continuity, Convergence, and Concentricity). The entrepreneurial spirit, through Dewantara’s lens, is manifested as an innovative “Pamong” leadership style that balances modernization with cultural roots and student-centered interests. Furthermore, the Niteni, Nirokke, Nambah (3-N) strategy serves as a practical framework for sustainable institutional innovation. This study concludes that the synthesis of modern management and local wisdom produces a humanistic entrepreneurial leadership model, enabling school organizational independence while preserving the core identity of national education.